Perspektif Komunikasi dalam Pembelajaran Jarak Jauh: Membangun Kehadiran Pengajar dan Kehadiran Sosial - Annisa Utami Seminar; Sarwititi Sarwoprasodjo (Jurnal Penyuluhan, 2023)
Covid-19 pandemic has changed the learning model in education to distance learning. The sudden change make students dissatisfy with the learning process thus declining the quality of learning. Research questions of this study are: (1) how to plan a distance learning that focus on building social presence? (2) how does message design of learning material contributes to social presence and student understanding?; and (3) how does the communication skills of the teacher contributes in building teaching presence? To answer these questions, this study used an action research design using class observation, in-depth interviews, and group interviews as data collection method. The action research design also acts to evaluate the research actions that have been given in the classroom. The findings of the study shows that the teaching presence in distance learning are determined from teachers’ communication skills which include: digital literacy, instructional roles or communicating messages in building classroom climate, as well as the ability to design message of learning material that can encourage the creation of social presence. This study also found that students’ understanding of the learning material also need to be encouraged by teachers’ ability in encouraging students to think analytically and critically.